Contraceptive Decision-Making and the Importance of Side Effect Information Among a Sample of Latinas - Gaia Cicerchia; Lawrence D. Reid; Diana N. Carvajal (Mary Ann Liebert, 2022)
Context: U.S. Latinas have lower rates of contraceptive use and report more negative counseling experiences compared to non-Latina white women. Patient-centered approaches to contraceptive counseling are desired among Latinas and are also associated with patient satisfaction; yet, clinicians may not always use counseling methods that best support decision-making among marginalized groups. Objective: To examine Latinas' expectations of physician communication about contraceptive side effects, reported importance of personal knowledge about side effects, and the association of these with contraceptive use and use consistency. Materials and Methods: One hundred three self-identified Latinas aged 15?29 years at two urban federally qualified health centers completed a survey measuring factors associated with contraceptive use and consistency. Bivariate analysis was used to assess demographic and contraceptive information preferences. Associations between categorical variables were assessed using two-sided Fisher's exact tests. Continuous variables were compared using two-sided t-test. Results: The majority of respondents (85%) expected physicians to tell them about birth control side effects and reported that this information is important to use contraception, regardless of current contraceptive use. Among inconsistent and nonusers, importance of knowledge of side effects depended on expectations of information-sharing from physicians (p?<?0.05). Conclusions: Expectations regarding side effect information-sharing by physicians and patient knowledge of side effects are important for the contraceptive decision-making process of this Latina group, regardless of contraceptive use. Clinicians engaging in contraceptive counseling should focus on providing clear and accurate information about side effects of discussed methods to facilitate informed decision-making and equitable, patient-centered contraceptive care for this vulnerable population.